The perceived work environment and well‐being: A survey of emergency health care workers during the COVID‐19 pandemic. (22nd May 2022) - Blanchard, Janice; Li, Yixuan; Bentley, Suzanne K.; Lall, Michelle D.; Messman, Anne M.; Liu, Yiju Teresa; Diercks, Deborah B.; Merritt‐Recchia, Rory; Sorge, Randy; Warchol, Jordan M.; Greene, Christopher; Griffith, James; et al.
Abstract: Background: During the COVID‐19 pandemic, health care provider well‐being was affected by various challenges in the work environment. The purpose of this study was to evaluate the relationship between the perceived work environment and mental well‐being of a sample of emergency physicians (EPs), emergency medicine (EM) nurses, and emergency medical services (EMS) providers during the pandemic. Methods: We surveyed attending EPs, resident EPs, EM nurses, and EMS providers from 10 academic sites across the United States. We used latent class analysis (LCA) to estimate the effect of the perceived work environment on screening positive for depression/anxiety and burnout controlling for respondent characteristics. We tested possible predictors in the multivariate regression models and included the predictors that were significant in the final model. Results: Our final sample included 701 emergency health care workers. Almost 23% of respondents screened positive for depression/anxiety and 39.7% for burnout. Nurses were significantly more likely to screen positive for depression/anxiety (adjusted odds ratio [aOR] 2.04, 95% confidence interval [CI] 1.11–3.86) and burnout (aOR 2.05, 95% CI 1.22–3.49) compared to attendings. The LCA analysis identified four subgroups of our respondents that differed in their responses to the work environment questions. These groups were identified as Work Environment Risk Group 1, an overall good work environment; Risk Group 2, inadequate resources; Risk Group 3, lack of perceived organizational support; and Risk Group 4, an overall poor work environment. Participants in the two groups who perceived their work conditions as most adverse were significantly more likely to screen positive for depression/anxiety (aOR 1.89, 95% CI 1.05–3.42; and aOR 2.04, 95% CI 1.14–3.66) compared to participants working in environments perceived as less adverse. Conclusions: We found a strong association between a perceived adverse working environment and poor mental health, particularly when organizational support was deemed inadequate. Targeted strategies to promote better perceptions of the workplace are needed.